Penerapan Prinsip Demokrasi dalam Sistem Pemilihan Umum di Indonesia Perspektif Fiqh Siyasah - Bustomi, Imam (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2023)
Since the reform era began in 1998 in Indonesia, political transformation has been significant. This period not only marked the end of the authoritarian government under President Soeharto, but also paved the way for changes in the political and constitutional system in Indonesia. This change not only changes the way of life of the people, but also changes the constitutional system of the Indonesian nation through amendments to the 1945 Constitution of the Republic of Indonesia. Article 1 paragraph (2) of the 1945 Constitution reads, "Sovereignty is in the hands of the people and is implemented according to the Constitution. In the Indonesian state administration there are also Islamic constitutional values, this can be seen by the concept of deliberation, equality and justice which is running as it should. This research aims to review the application of democratic principles in general elections and how Islamic state administration is reviewed (fiqh siyasah ) in the implementation of general elections in Indonesia. Through a normative juridical approach, this research analyzes the regulations governing the democracy and election system in Indonesia, including the 1945 Constitution and the Election Law. Research highlights the importance of implementing democratic principles such as popular sovereignty, equal rights, free and secret elections, and accountability and transparency in the electoral process. However, challenges such as money politics, identity politics and the spread of false information are still problems in the implementation of elections. This research suggests steps to improve the electoral system to ensure that democracy can function effectively and produce results that are more representative of the will of the people and that it is in accordance with Islamic constitutional principles (fiqh siyasah)